Application and preparation method of diversified agricultural bentonite
Through a preparation method of plural agricultural bentonite, the problem of low product quality and process level in bentonite application is solved, and multifunctional agricultural bentonite is realized, which significantly improves the soil's water retention, fertilizer retention ability and crop growth conditions. It is suitable for Various agricultural fields.
Patent Information
- Application Number
- CN202510054271.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-02-18
AI Technical Summary
In the development and application of bentonite, there are problems such as low product quality, low process level, poor economic benefits and poor universality, which leads to low competition in the industry and low technical level, making it difficult to scale.
A method of preparation of polysilicon agricultural bentonite, including crushing bentonite and obtaining sodium-based bentonite by double sodiumization, followed by sodium carboxymethylcellulose, modified carbon powder, sodium dodecylbenzenesulfonate, citric acid Aluminum, polyacrylamide and deionized water are mixed at high speed, dried, ball milled and screened, and finally mixed with magnesium oxide, microcrystalline cellulose, diatomaceous earth and modified hemp fibers, calcined and cooled to form activated bentonite powder. It is mixed with chitosan solution and then treated with a constant temperature, and finally obtained polysilicon agricultural bentonite by drying.
The prepared multi-purpose agricultural bentonite has many advantages in the agricultural field, including improving soil structure, improving soil water retention and fertilizer retention capacity, reducing fertilizer moisture content, preventing fertilizer clumping, and improving fertilizer particle size and utilization rate. It is suitable for soil improvement agents, fertilizer conditioners, fertilizer carriers and microbial agents, and has the effect of significantly improving the physical properties and biological activities of the soil, promoting crop growth and environmental protection.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bentonite materials, and in particular to the application of multi-element agricultural bentonite and a preparation method thereof. Background Art
[0002] Bentonite is also known as bentonite, bentonite or bentonite. Its main mineral component is montmorillonite. Some of the properties of bentonite are also determined by montmorillonite. There are many types of bentonite, each with different mineral composition, physical properties and industrial applications.
[0003] At present, the main problems in the development and application of bentonite are: low product quality, low process level, poor economic benefits, poor universality, etc. As a result, the bentonite industry has low competition, low technical level and difficulty in scale.
[0004] Therefore, there is a need for an application of multi-functional agricultural bentonite and a preparation method thereof to solve the above-described problems. Summary of the invention
[0005] The purpose of the present invention is to provide an application of multi-element agricultural bentonite and a preparation method thereof to solve the above problems.
[0006] The scheme of the present invention is A method for preparing multi-functional agricultural bentonite comprises the following steps: 1) The bentonite is crushed, passed through a 500-mesh sieve, and double sodiumized to obtain sodium-based bentonite; 2) sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water are put into a mixer, and mixed at a high speed of 800 to 1200 rpm for 30 to 60 minutes. After the mixture is obtained, it is dried in an oven at 110°C, ball-milled, and passed through a 400-mesh sieve to obtain primary bentonite; the mass ratio of the sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water is 100 to 120: 0.2 to 1: 3 to 6: 0.1 to 0.2: 0.05 to 0.2: 5 to 6: 200 to 400; 3) Mixing sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth, calcining for 1 to 2 hours, and cooling to obtain activated bentonite powder; the mass ratio of the sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth is 60 to 80:40 to 55:1 to 5:5 to 10:30 to 40; 4) The modified hemp fiber is crushed, passed through a 400-mesh sieve, and the sieve residue is taken to obtain a modified fiber powder; the coal slag and biogas residue are crushed separately, passed through a 400-mesh sieve, and mixed in a ratio of 3 to 5:1 to obtain a mixture; 5) Mixing the activated bentonite powder, the mixture, the modified fiber powder and deionized water to form a suspension; 6) Dissolve chitosan in 4-6% acetic acid solution to fully dissolve it, add the suspension thereto, treat with ultrasound for 60-90 minutes, react at a constant temperature for 1-2 hours, and dry to obtain multi-element agricultural bentonite.
[0007] As a preferred technical solution, the modified carbon powder includes modified wood carbon powder and modified coal carbon powder, and the mass ratio of the modified wood carbon powder to the modified coal carbon powder is 7:3.
[0008] As a preferred technical solution, the mass volume ratio of activated bentonite powder, mixture, modified fiber powder, deionized water, chitosan and acetic acid is 25-30g:15-20g:5-8g:30ml:0.25-0.75g:50ml; in the step 6), the constant temperature is 35-40°C, the drying temperature is 70-80°C, and the drying time is 20-24h; the mixing in step 5) is stirring mixing, the stirring speed is 150-250r / min, and the time is 1-2h.
[0009] As a preferred technical solution, the preparation method of the modified wood charcoal powder is: Add polyvinyl alcohol into water and stir evenly, let it stand for 4 to 6 hours, then stir for 10 to 20 minutes, the stirring speed is 800 to 1000 r / min, add fatty acid glyceride and coconut oil and stir for 2 to 3 minutes, the stirring speed is 300 to 500 r / min, then add hexadecyl trimethyl ammonium bromide and sodium hydroxide and stir for 2 to 3 minutes, the stirring speed is 300 to 500 r / min, N, N-methylene bis acrylamide and stir for 2 to 3 minutes, the speed is 300 to 500 r / min, then add wood charcoal powder while stirring, stir for 6 to 8 hours, the stirring speed is 500 to 600 r / min, after mixing, send it into granulation equipment, extrude it into granular carbon, bake the granular carbon to a moisture content of ≤5%, the baking temperature is 70 to 120°C, and the baking time is 6 to 10 hours; send the baked granular carbon into a crushing equipment for crushing, and sieve it after crushing to obtain modified wood charcoal powder.
[0010] The modified wood charcoal powder comprises the following raw materials in parts by weight: 15-20 parts of polyvinyl alcohol, 0.2-2 parts of fatty acid glyceride, 0.3-3 parts of coconut oil, 0.05-0.1 parts of hexadecyl trimethyl ammonium bromide, 0.4-4 parts of sodium hydroxide, 0.5-2 parts of N,N-methylenebisacrylamide, 100-110 parts of wood carbon powder, and 100-110 parts of deionized water. The wood powder charcoal is a wood powder activated carbon produced by phosphoric acid method with a mesh number of ≥200 mesh, an iodine value of ≥1100 mg / g, and a pH value of ≥5.6. The polyvinyl alcohol is one or a combination of PVA1792, PVA1799, PVA2099, PVA2092, PVA2499, and PVA2492.
[0011] As a preferred technical solution, the preparation method of the modified coal-based carbon powder is: Add urea, humic acid, sodium hexaphosphate, polyethylene glycol and sodium carbonate into water and stir evenly, let stand for 4 to 6 minutes, add sodium dodecyl sulfate and stir evenly, add coal-based columnar carbon while stirring, stir for 1 to 2 hours, bake until the moisture content is ≤5%, crush and sieve to obtain modified coal-based carbon powder.
[0012] The modified coal-based carbon powder comprises the following raw materials in parts by weight: 5-15 parts of urea, 5-10 parts of humic acid, 0.2-2 parts of sodium hexaphosphate, 0.1-1 parts of polyethylene glycol, 1-5 parts of sodium carbonate, 100-120 parts of water, 0.5-3 parts of sodium dodecyl sulfonate, and 100-120 parts of coal-based columnar carbon. The coal-based columnar carbon is a coal-based columnar activated carbon with a CTC value of ≥50%, a particle size of 0.9-9 mm, an iodine value of ≥800 mg / g, and an ash content of ≤5%.
[0013] As a preferred technical solution, the grinding medium used in the ball mill is a zirconium oxide ball, the diameter of the grinding medium is between 5 and 20 mm, and the mass ratio of the grinding medium to the material is 1:2.
[0014] As a preferred technical solution, the preparation method of the modified hemp fiber is: Purified lignin, calcium titanate and ultrapure water were mixed, magnetically stirred for 10 minutes, and ultrasonically dispersed for 0.5 hours to obtain a mixed solution; The jute fiber was washed and drained in deionized water, and then transferred to an oven for drying at 50-60°C. After drying, it was chopped into 0.5-1 mm and passed through a 100-mesh sieve. The sieved jute fiber was immersed in a 1 mol / L sodium hydroxide solution with a solid-liquid mass volume ratio of 1g:5mL. After soaking for 12 hours, it was washed with distilled water until neutral. Then the jute fiber was obtained and placed in a constant temperature blast drying oven for drying at 60°C for 8 hours. The dried jute fiber was immersed in the mixed solution for 1 hour at room temperature with magnetic stirring. After washing with deionized water until neutral, it was placed in a vacuum drying oven at 60°C for 8 hours to obtain modified jute fiber.
[0015] The modified hemp fiber comprises the following raw materials in parts by weight: 40-60 parts of purified lignin, 0.05-0.5 parts of calcium titanate, 1300-1500 parts of ultrapure water, and 40-60 parts of jute fiber.
[0016] The invention also discloses a method for preparing multi-component agricultural bentonite and the application of the multi-component agricultural bentonite in agriculture.
[0017] As a preferred technical solution, the multi-property agricultural bentonite is used as a soil conditioner, a fertilizer conditioner, a fertilizer carrier, a microbial agent carrier and a fertilizer granulator.
[0018] The invention adopts a multi-element agricultural bentonite application and a preparation method thereof, comprising the following steps: 1) crushing bentonite, passing through a 500-mesh sieve, and obtaining sodium-based bentonite through double sodiumization; 2) putting sodium-based bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecyl benzene sulfonate, aluminum citrate, polyacrylamide and deionized water into a mixer, and mixing at a high speed for 30 to 60 minutes at a rotation speed of 800 to 1200 rpm to obtain a mixed material, drying in an oven at 110°C, ball milling, passing through a 400-mesh sieve, and obtaining primary bentonite; the mass ratio of the sodium-based bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecyl benzene sulfonate, aluminum citrate, polyacrylamide and deionized water is 100 to 120:0.2 to 1:3 to 6:0.1 to 0.2:0.05 to 0.2:5 to 6:200 to 400; 3) mixing the sodium-based bentonite, primary bentonite and the mixture; Mix bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth, calcine for 1 to 2 hours, and obtain activated bentonite powder after cooling; the mass ratio of the sodium-based bentonite, primary bentonite mixture, magnesium oxide, microcrystalline cellulose and diatomaceous earth is 60 to 80:40 to 55:1 to 5:5 to 10:30 to 40; 4) grind the modified hemp fiber, pass it through a 400-mesh sieve, take the sieve under the sieve to obtain modified fiber powder; grind coal slag and biogas residue separately, pass them through a 400-mesh sieve, and mix them in a ratio of 3 to 5:1 to obtain a mixture; 5) mix the activated bentonite powder, the mixture, the modified fiber powder and deionized water to form a suspension; 6) dissolve chitosan in an acetic acid solution with a volume percentage concentration of 4 to 6% to fully dissolve it, add the suspension thereto, ultrasonically treat it for 60 to 90 minutes, react at a constant temperature for 1 to 2 hours, and dry it to obtain multi-element agricultural bentonite.
[0019] Advantages of the present invention: The multi-functional agricultural bentonite prepared by the present invention is applicable to multiple fields of agriculture and is applied to soil conditioners. After being applied to the soil, it can absorb water and swell, change the soil structure, make it loose, improve the physical properties of the soil, and enhance the water and fertilizer retention capacity of the soil. Applied to fertilizer conditioners, it can reduce the water content of fertilizers, prevent fertilizers from agglomerating, increase the particle size of fertilizers, and facilitate the transportation and use of fertilizers; As a fertilizer carrier, it can improve the physical properties of fertilizers, increase fertilizer stability, reduce fertilizer losses in the soil, improve fertilizer utilization, and promote crop yields by regulating fertilizers. It is used in fertilizer granulation and can be used as compound fertilizer granulating agent after processing. It has the characteristics of fast granulation speed, high ball formation rate, uniform particles, smooth surface, high particle strength, etc., which saves production costs.
[0020] The bentonite prepared by the present invention can also be mixed with waste from edible fungus cultivation to prepare a composite agent, which can enhance water retention performance, reduce nutrient loss, and play a role in water and fertilizer retention.
[0021] In practical applications, it can also be mixed with organic fertilizers to increase soil moisture and organic matter content, improve soil structure, and improve crop growth conditions and yields.
[0022] Through its high water conductivity, it helps plant roots absorb water and nutrients, thereby improving the survival rate of seedlings.
[0023] The bentonite prepared by the invention is mixed with small-molecule peptide chelated peptide type trace elements for use to improve soil fertility and soil structure, thereby greatly reducing the occurrence of soil-borne diseases and crop physiological diseases.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. The performance of the bentonite prepared by the method of the present invention is significantly improved, and it can play a greater role in the agricultural field, especially in arid and desertified areas, and can significantly improve the survival rate and growth conditions of plants; in particular, when mixed with sand, the water holding capacity and fertility of the sand are improved, and the growth of crops is promoted. In addition, the bentonite can also be compounded with other materials to form a sand-fixing material for desertification control and ecological restoration.
[0025] 2. As a soil conditioner, it improves the physical properties of the soil, increases the soil's water retention capacity and air permeability, and thus helps plants absorb water and nutrients better. The soil conditioner made by compounding bentonite with chelated small molecule peptides and trace elements has a good preventive and therapeutic effect on soil-borne diseases. Soil improvement can be carried out through the following points.
[0026] Improve soil structure. The bentonite prepared by the present invention can be applied to sandy soil to significantly reduce soil bulk density, increase soil water storage capacity and macroaggregate content and stability.
[0027] The water and fertilizer retention capacity of the soil is improved. The bentonite prepared by the present invention is used as a fertilizer slow-control carrier to reduce the amount of fertilizer washed away by water and improve the soil's ability to store fertilizer and water.
[0028] Adjusting soil pH: The bentonite prepared by the present invention can adjust the ratio of the three phases of solid, liquid and gas in the soil after application, thereby improving the physical and chemical properties of the soil.
[0029] Increasing soil microbial activity. The application of the bentonite prepared by the present invention can effectively increase the microbial biomass and enzyme activity in the soil.
[0030] Providing the nutrients required by plants, the bentonite prepared by the present invention carries S, AI, Fe, Mg, Ca and other macro or trace nutrients required by various plants, which can also promote the growth of crops.
[0031] Reducing soil-borne diseases: The application of the bentonite prepared by the present invention helps to reduce the number of pathogens in the soil and reduce the occurrence of soil-borne diseases.
[0032] Improve crop yield. After applying the bentonite prepared by the present invention to crops such as corn and wheat in the farmland of the Hetao irrigation area, the yield is improved.
[0033] The bentonite prepared by the present invention promotes the development of crop roots, and its application helps to promote the absorption of nutrients by crop roots, thereby increasing the growth rate of crops.
[0034] Environmentally friendly, the bentonite prepared by the invention is a green and environmentally friendly soil improvement material, has little disturbance to the environment, and has abundant reserves and low prices.
[0035] 3. The bentonite prepared by the present invention is used as a water-soluble drip irrigation fertilizer. The bentonite has good water absorption and swelling properties, can be dispersed into a gelled and suspended state in a water medium, and has certain viscosity, thixotropy and lubricity. These properties enable the bentonite to be used as a soil conditioner in agriculture, helping to improve soil structure and enhance the soil's water and fertilizer retention capacity.
[0036] 4. The bentonite prepared by the present invention can be used as a carrier of microbial agents due to its unique physical and chemical properties. It has a large specific surface area and cation exchange capacity, and can adsorb and fix microorganisms, thus preserving Protect microorganisms from adverse external environments .
[0037] When preparing microbial agents, bentonite can be used as a carrier to help microorganisms colonize and reproduce in the soil.
[0038] In application, the composite microbial agent coated with bentonite prepared by the present invention can increase the compressive strength of the granular microbial agent, maintain the relative stability of the internal environment of the coated agent, prevent the reduction of the number of live microorganisms due to water loss, and ensure the product quality. After being applied to the soil, the bentonite can reduce the relative density of the soil, increase the water content of the soil, slow down the water loss, and maintain it for a long time, which can play a very important role in maintaining the moisture content in the soil in arid areas.
[0039] In addition, it has a good effect on coordinating the water, fertilizer, gas and heat of the soil and improving soil fertility, which can contribute to the formation of soil structure, improve the soil's ability to retain fertilizer and water, and improve the soil's water and heat conditions. Therefore, the bentonite-coated microbial agent prepared by the present invention can not only be used as a fertilizer to promote crop growth, but also improve the soil environment and improve the stress resistance of crops. As a filler or carrier of the microbial agent, it can not only improve the physical properties of the agent, but also help the survival and reproduction of microorganisms in the soil, thereby improving the growth conditions and yield of crops.
[0040] 5. Provide a usable material for seed coating and stress resistance products. DETAILED DESCRIPTION
[0041] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0042] The double sodiumization method of sodium-based bentonite in the embodiment of the present invention: 1) mixing calcium bentonite with sodium salt and sodiumizing the mixture to obtain primary sodium bentonite; 2) mixing the primary sodium bentonite with an additive and inoculating to obtain the secondary sodium bentonite; The additives include microcrystalline cellulose, sodium salt-modified silica gel, expanded vermiculite, ammonium borate, a thickener and polyacrylamide; the sodium salt is sodium silicate, and the sodium salt in the sodium salt-modified silica gel is sodium chloride; the thickener is selected from magnesium oxide; relative to 100 parts by weight of the sodium salt-modified silica gel, the content of the microcrystalline cellulose is 10 parts by weight, the content of the expanded vermiculite is 50 parts by weight, the content of the ammonium borate is 5 parts by weight, the content of the thickener is 2 parts by weight, and the content of the polyacrylamide is 3 parts by weight.
[0043] The weight ratio of the calcium-based bentonite to the sodium salt is 100:3.
[0044] The sodiumization temperature is 15-35°C, and the sodiumization time is 24-30h.
[0045] The content of sodium salt in the sodium salt-modified silica gel is 5-10% by weight.
[0046] The particle sizes of the expanded vermiculite and the sodium salt modified silica gel are independently not less than 200 meshes.
[0047] The weight average molecular weight of the polyacrylamide is 4 million to 10 million.
[0048] The weight ratio of the primary sodium bentonite to the additive is 100:35.
[0049] The incubation at least meets the following conditions: the incubation temperature is 15-35° C., and the incubation time is 3-7 days.
[0050] Embodiment 1: 1) The bentonite is crushed, passed through a 500-mesh sieve, and double sodiumized to obtain sodium-based bentonite; 2) sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water are put into a mixer and mixed at a high speed of 800 rpm for 300 minutes. After the mixture is obtained, it is dried in an oven at 110° C., ball-milled, and passed through a 400-mesh sieve to obtain primary bentonite; the mass ratio of the sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water is 100:0.2:3:0.1:0.05:5:200; 3) Mixing sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth, calcining for 1 hour, and cooling to obtain activated bentonite powder; the mass ratio of the sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth is 60:40:1:5:30; 4) The modified hemp fiber is crushed, passed through a 400-mesh sieve, and the sieve residue is taken to obtain a modified fiber powder; coal slag and biogas residue are crushed separately, passed through a 400-mesh sieve, and mixed in a ratio of 3:1 to obtain a mixture; 5) Mixing the activated bentonite powder, the mixture, the modified fiber powder and deionized water to form a suspension; 6) Dissolve chitosan in acetic acid solution with a volume percentage concentration of 5% to fully dissolve it, add the suspension thereto, treat with ultrasound for 60 minutes, react at a constant temperature for 1 hour, and dry to obtain multi-element agricultural bentonite.
[0051] The modified carbon powder includes modified wood carbon powder and modified coal carbon powder, and the mass ratio of the modified wood carbon powder to the modified coal carbon powder is 7:3.
[0052] The mass volume ratio of activated bentonite powder, mixture, modified fiber powder, deionized water, chitosan and acetic acid is 25g:15g:5-8g:30ml:0.255g:50ml; in the step 6), the constant temperature is 35°C, the drying temperature is 70°C, and the drying time is 20h; the mixing in the step 5) is stirring mixing, the stirring speed is 150r / min, and the time is 1h.
[0053] The preparation method of the modified wood charcoal powder is: Add polyvinyl alcohol into water and stir evenly. After standing for 4 hours, stir for 10 minutes at a stirring speed of 800 r / min. Add fatty acid glyceride and coconut oil and stir for 2 minutes at a stirring speed of 300 r / min. Then add hexadecyltrimethylammonium bromide and sodium hydroxide and stir for 2 minutes at a stirring speed of 300 r / min. Stir N,N-methylenebisacrylamide for 2 minutes at a speed of 300 r / min. Then add wood charcoal powder while stirring, stir for 6 hours at a stirring speed of 500 r / min. After mixing, send it to a granulation equipment and extrude it into granular carbon. Bake the granular carbon to a moisture content of ≤5% at a baking temperature of 70°C for 6 hours. Send the baked granular carbon to a crushing equipment for crushing, and sieve it after crushing to obtain modified wood charcoal powder.
[0054] The modified wood charcoal powder comprises the following raw materials in parts by weight: 15 parts of polyvinyl alcohol, 0.2 parts of fatty acid glyceride, 0.3 parts of coconut oil, 0.05 parts of hexadecyltrimethylammonium bromide, 0.4 parts of sodium hydroxide, 0.5 parts of N,N-methylenebisacrylamide, 100 parts of wood carbon powder, and 100 parts of deionized water. The wood powder charcoal is a wood powder activated carbon produced by a phosphoric acid method with a mesh number of ≥200 mesh, an iodine value of ≥1100 mg / g, and a pH value of ≥5.6. The polyvinyl alcohol is PVA1792.
[0055] The preparation method of the modified coal-based carbon powder is: Urea, humic acid, sodium hexaphosphate, polyethylene glycol and sodium carbonate were added to water and stirred evenly. After standing for 4 minutes, sodium dodecyl sulfate was added and stirred evenly. Coal-based columnar carbon was added while stirring and stirred for 1 hour. The mixture was baked until the moisture content was ≤5%, crushed and sieved to obtain modified coal-based carbon powder. The stirring speed was 300 r / min. The modified coal-based carbon powder includes the following raw materials in parts by weight: 5 parts of urea, 5 parts of humic acid, 0.2 parts of sodium hexaphosphate, 0.1 parts of polyethylene glycol, 1 part of sodium carbonate, 100 parts of water, 0.5 parts of sodium dodecyl sulfate, and 100 parts of coal-based columnar carbon. The coal-based columnar carbon is a coal-based columnar activated carbon with a CTC value of ≥50%, a particle size of 0.9-9 mm, an iodine value of ≥800 mg / g, and an ash content of ≤5%.
[0056] The grinding medium used in the ball mill is a zirconium oxide ball, the diameter of the grinding medium is between 5 and 20 mm, and the mass ratio of the grinding medium to the material is 1:2.
[0057] The preparation method of the modified hemp fiber is: Purified lignin, calcium titanate and ultrapure water were mixed, magnetically stirred for 10 minutes, and ultrasonically dispersed for 0.5 hours to obtain a mixed solution; The jute fiber was washed and drained in deionized water, transferred to an oven and dried at 50°C, chopped into 0.5-1 mm after drying, passed through a 100-mesh sieve, and the sieved jute fiber was immersed in a 1 mol / L sodium hydroxide solution with a solid-liquid mass volume ratio of 1g:5mL. After soaking for 12 hours, it was washed with distilled water until neutral, and then the jute fiber was obtained and placed in a constant temperature blast drying oven at 60°C for 8 hours; the dried jute fiber was immersed in the mixed solution at room temperature for 1 hour with magnetic stirring; it was washed with deionized water until neutral and then placed in a vacuum drying oven at 60°C for 8 hours to obtain modified jute fiber.
[0058] The modified hemp fiber comprises the following raw materials in parts by weight: 40 parts of purified lignin, 0.05 parts of calcium titanate, 1300 parts of ultrapure water, and 40 parts of jute fiber.
[0059] Embodiment 2: 1) The bentonite is crushed, passed through a 500-mesh sieve, and double sodiumized to obtain sodium-based bentonite; 2) sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water are put into a mixer and mixed at a high speed of 1200 rpm for 60 minutes. After the mixture is obtained, it is dried in an oven at 110° C., ball-milled, and passed through a 400-mesh sieve to obtain primary bentonite; the mass ratio of the sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water is 120:1:6:0.2:0.2:6:400; 3) Mixing sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth, calcining for 2 hours, and cooling to obtain activated bentonite powder; the mass ratio of sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth is 80:55:5:10:40; 4) The modified hemp fiber is crushed, passed through a 400-mesh sieve, and the sieve residue is taken to obtain a modified fiber powder; coal slag and biogas residue are crushed separately, passed through a 400-mesh sieve, and mixed in a ratio of 5:1 to obtain a mixture; 5) Mixing the activated bentonite powder, the mixture, the modified fiber powder and deionized water to form a suspension; 6) Dissolve chitosan in acetic acid solution with a volume percentage concentration of 5% to fully dissolve it, add the suspension thereto, treat with ultrasound for 90 minutes, react at a constant temperature for 2 hours, and dry to obtain multi-element agricultural bentonite.
[0060] The modified carbon powder includes modified wood carbon powder and modified coal carbon powder, and the mass ratio of the modified wood carbon powder to the modified coal carbon powder is 7:3.
[0061] The mass volume ratio of activated bentonite powder, mixture, modified fiber powder, deionized water, chitosan and acetic acid is 30g:20g:8g:30ml:0.75g:50ml; in the step 6), the constant temperature is 40°C, the drying temperature is 80°C, and the drying time is 24h; the mixing in step 5) is stirring mixing, the stirring speed is 250r / min, and the time is 2h.
[0062] The preparation method of the modified wood charcoal powder is: Add polyvinyl alcohol into water and stir evenly. After standing for 6 hours, stir for 20 minutes at a stirring speed of 1000 r / min. Add fatty acid glyceride and coconut oil and stir for 3 minutes at a stirring speed of 500 r / min. Then add hexadecyltrimethylammonium bromide and sodium hydroxide and stir for 3 minutes at a stirring speed of 500 r / min. Stir N,N-methylenebisacrylamide for 3 minutes at a speed of 500 r / min. Then add wood charcoal powder while stirring, stir for 8 hours at a stirring speed of 600 r / min. After mixing, send the mixed materials into a granulating device and extrude them into granular charcoal. Bake the granular charcoal to a moisture content of ≤5% at a baking temperature of 120°C for 10 hours. Send the baked granular charcoal into a crushing device for crushing, and sieve after crushing to obtain modified wood charcoal powder.
[0063] The modified wood charcoal powder comprises the following raw materials in parts by weight: 20 parts of polyvinyl alcohol, 2 parts of fatty acid glyceride, 3 parts of coconut oil, 0.1 parts of hexadecyltrimethylammonium bromide, 4 parts of sodium hydroxide, 2 parts of N,N-methylenebisacrylamide, 110 parts of wood carbon powder, and 110 parts of deionized water. The wood powder charcoal is a wood powder activated carbon produced by a phosphoric acid method with a mesh number of ≥200 mesh, an iodine value of ≥1100 mg / g, and a pH value of ≥5.6. The polyvinyl alcohol is PVA2492.
[0064] The preparation method of the modified coal-based carbon powder is: Add urea, humic acid, sodium hexaphosphate, polyethylene glycol and sodium carbonate into water and stir evenly, let stand for 6 minutes, add sodium dodecyl sulfate and stir evenly, add coal-based columnar charcoal while stirring, stir for 2 hours, bake until the moisture content is ≤5%, crush and sieve to obtain modified coal-based charcoal powder.
[0065] The modified coal-based carbon powder comprises the following raw materials in parts by weight: 15 parts of urea, 10 parts of humic acid, 2 parts of sodium hexaphosphate, 1 part of polyethylene glycol, 5 parts of sodium carbonate, 120 parts of water, 3 parts of sodium dodecyl sulfate, and 120 parts of coal-based columnar carbon. The coal-based columnar carbon is a coal-based columnar activated carbon with a CTC value of ≥50%, a particle size of 0.9-9 mm, an iodine value of ≥800 mg / g, and an ash content of ≤5%.
[0066] The grinding medium used in the ball mill is a zirconium oxide ball, the diameter of the grinding medium is between 5 and 20 mm, and the mass ratio of the grinding medium to the material is 1:2.
[0067] The preparation method of the modified hemp fiber is: Purified lignin, calcium titanate and ultrapure water were mixed, magnetically stirred for 10 minutes, and ultrasonically dispersed for 0.5 hours to obtain a mixed solution; The jute fiber was washed and drained in deionized water, transferred to an oven and dried at 60°C, chopped into 0.5-1 mm after drying, passed through a 100-mesh sieve, and the sieved jute fiber was immersed in a 1 mol / L sodium hydroxide solution with a solid-liquid mass volume ratio of 1g:5mL. After soaking for 12 hours, it was washed with distilled water until neutral, and then the jute fiber was obtained and placed in a constant temperature blast drying oven at 60°C for 8 hours; the dried jute fiber was immersed in the mixed solution at room temperature for 1 hour with magnetic stirring; it was washed with deionized water until neutral and then placed in a vacuum drying oven at 60°C for 8 hours to obtain modified jute fiber.
[0068] The modified hemp fiber comprises the following raw materials in parts by weight: 60 parts of purified lignin, 0.5 parts of calcium titanate, 1500 parts of ultrapure water, and 60 parts of jute fiber.
[0069] Embodiment 3: 1) The bentonite is crushed, passed through a 500-mesh sieve, and double sodiumized to obtain sodium-based bentonite; 2) sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water are put into a mixer and mixed at a high speed of 1000 rpm for 40 min to obtain a mixture, which is then dried in an oven at 110° C., ball-milled and passed through a 400-mesh sieve to obtain primary bentonite; the mass ratio of the sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water is 100:0.5:4:0.1:0.1:5:200; 3) Mixing sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth, calcining for 1 to 2 hours, and cooling to obtain activated bentonite powder; the mass ratio of the sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth is 70:45:2:7:35; 4) grinding the modified hemp fiber, passing it through a 400-mesh sieve, taking the sieved material to obtain modified fiber powder; grinding the coal slag and biogas residue separately, passing them through a 400-mesh sieve, and mixing them in a ratio of 4:1 to obtain a mixture; 5) Mixing the activated bentonite powder, the mixture, the modified fiber powder and deionized water to form a suspension; 6) Dissolve chitosan in acetic acid solution with a volume percentage concentration of 5% to fully dissolve it, add the suspension thereto, treat with ultrasound for 60 minutes, react at a constant temperature for 2 hours, and dry to obtain multi-element agricultural bentonite.
[0070] The modified carbon powder includes modified wood carbon powder and modified coal carbon powder, and the mass ratio of the modified wood carbon powder to the modified coal carbon powder is 7:3.
[0071] The mass volume ratio of activated bentonite powder, mixture, modified fiber powder, deionized water, chitosan and acetic acid is 30g:15g:5g:30ml:0.5g:50ml; in the step 6), the constant temperature is 40°C, the drying temperature is 80°C, and the drying time is 24h; the mixing in the step 5) is stirring mixing, the stirring speed is 200r / min, and the time is 2h.
[0072] The preparation method of the modified wood charcoal powder is: Add polyvinyl alcohol into water and stir evenly. After standing for 5 hours, stir for 20 minutes at a stirring speed of 1000 r / min. Add fatty acid glyceride and coconut oil and stir for 3 minutes at a stirring speed of 400 r / min. Then add hexadecyl trimethyl bromide and sodium hydroxide and stir for 3 minutes at a stirring speed of 400 r / min. Stir N,N-methylenebisacrylamide for 3 minutes at a speed of 400 r / min. Then add wood charcoal powder while stirring, stir for 6 hours at a stirring speed of 500 r / min. After mixing, send it to a granulation equipment and extrude it into granular carbon. Bake the granular carbon to a moisture content of ≤5% at a baking temperature of 80°C for 8 hours. Send the baked granular carbon to a crushing equipment for crushing, and sieve it after crushing to obtain modified wood charcoal powder.
[0073] The modified wood carbon powder comprises the following raw materials in parts by weight: 18 parts of polyvinyl alcohol, 0.5 parts of fatty acid glyceride, 1 part of coconut oil, 0.05 parts of hexadecyltrimethylammonium bromide, 2 parts of sodium hydroxide, 1 part of N,N-methylenebisacrylamide, 105 parts of wood carbon powder, and 105 parts of deionized water.
[0074] The wood powder carbon is wood powder activated carbon produced by phosphoric acid method with mesh size ≥200 mesh, iodine value ≥1100 mg / g, and pH value ≥5.6. The polyvinyl alcohol is PVA2099.
[0075] The preparation method of the modified coal-based carbon powder is: Add urea, humic acid, sodium hexaphosphate, polyethylene glycol and sodium carbonate into water and stir evenly, let stand for 5 minutes, add sodium dodecyl sulfate and stir evenly, add coal-based columnar charcoal while stirring, stir for 2 hours, bake until the moisture content is ≤5%, crush and sieve to obtain modified coal-based charcoal powder.
[0076] The modified coal-based carbon powder comprises the following raw materials in parts by weight: 10 parts of urea, 8 parts of humic acid, 0.5 parts of sodium hexaphosphate, 0.5 parts of polyethylene glycol, 3 parts of sodium carbonate, 100 parts of water, 1 part of sodium dodecyl sulfate, and 100 parts of coal-based columnar carbon. The coal-based columnar carbon is a coal-based columnar activated carbon with a CTC value of ≥50%, a particle size of 0.9-9 mm, an iodine value of ≥800 mg / g, and an ash content of ≤5%.
[0077] The grinding medium used in the ball mill is a zirconium oxide ball, the diameter of the grinding medium is between 5 and 20 mm, and the mass ratio of the grinding medium to the material is 1:2.
[0078] The preparation method of the modified hemp fiber is: Purified lignin, calcium titanate and ultrapure water were mixed, magnetically stirred for 10 minutes, and ultrasonically dispersed for 0.5 hours to obtain a mixed solution; The jute fiber was washed and drained in deionized water, transferred to an oven and dried at 60°C, chopped into 0.5-1 mm after drying, passed through a 100-mesh sieve, and the sieved jute fiber was immersed in a 1 mol / L sodium hydroxide solution with a solid-liquid mass volume ratio of 1g:5mL. After soaking for 12 hours, it was washed with distilled water until neutral, and then the jute fiber was obtained and placed in a constant temperature blast drying oven at 60°C for 8 hours; the dried jute fiber was immersed in the mixed solution at room temperature for 1 hour with magnetic stirring; it was washed with deionized water until neutral and then placed in a vacuum drying oven at 60°C for 8 hours to obtain modified jute fiber.
[0079] The modified hemp fiber comprises the following raw materials in parts by weight: 450 parts of purified lignin, 0.1 parts of calcium titanate, 1500 parts of ultrapure water, and 50 parts of jute fiber.
[0080] The following experiments were carried out in Example 3.
[0081] Experiment 1 A 25 cm deep ditch was dug to simulate the surface of the sandy land, and the microbial liquid was sprayed into the ditch, and organic humus was added and then the ditch was buried; Comparative Example 1 was prepared according to the method of Example 3 in Patent Application No. CN201710734474.2 A sand-fixing composition and its preparation method and application, and the multi-component agricultural bentonite prepared in Example 3 of the present invention was substituted for the bentonite used in Example 3 to obtain a comparative example; The first pre-liquid and the second pre-liquid prepared in the above-mentioned Example and Comparative Example 1 were sprayed on the sand surface of the sand fixation area at a volume ratio of 2:1; wherein the spraying amount was 3 kg / m2. After the sand fixation bonding layer was formed, the wind erosion resistance, compressive strength, freeze-thaw resistance, strength loss rate, mass loss rate, anti-aging, moisture retention and other indicators were statistically analyzed. The specific results are shown in Table 1.
[0082] in: Thickness of sand-fixing binding layer: After the sand-fixing binding layer is stably formed, its thickness is measured.
[0083] Wind erosion resistance: The mass loss rate and strength loss rate of the sand-fixing bonding layer are measured under a specific wind speed.
[0084] Compressive strength: After the sand-fixing bonding layer is stably formed, its compressive strength is calculated.
[0085] Freeze-thaw resistance: Under multiple freeze-thaw cycles, the strength loss rate (referred to as strength loss) and mass loss rate (referred to as mass loss) of the sand-fixing binding layer are calculated.
[0086] Anti-aging: Under the condition of continuous ultraviolet light irradiation, the strength loss rate of the sand-fixing bonding layer was calculated.
[0087] Moisture retention: Dry the formed sand-fixing bonding layer in a drying oven and count the moisture retention.
[0088] Thermal insulation: Under a specific light intensity, the effect of the sand-fixing bonding layer on the temperature of the bottom substrate was statistically studied.
[0089] Table 1: Statistics of test results of participating cases and comparison cases Grouping Sand fixation thickness (mm) Compressive strength (MPa) Wind resistance (one month under 20km / h wind speed condition) Freeze-thaw resistance (20 cycles of treatment at a temperature difference greater than 50°C) Anti-aging (UV irradiation 200h) Moisture retention (water loss rate after 3 hours in a 40°C drying oven) Thermal insulation (statistical temperature difference between both ends of the bonding layer after standing at 30℃ for 4 hours) Participation Example 14 0.6 Quality loss: 7% Strength loss: 4% Quality loss: 0.7% Strength loss: 3% 21% 9% 11℃ Comparative Example 14 0.9 Quality loss: 5% Strong damage: 2% Quality loss: 0.4% Strength loss: 3 18% 7% 11℃ In summary, the present application can be used for sand fixation, and has the effect of sand fixation and soil repair and improvement.
[0090] Experiment 2 Nutrient improvement trial Dissolve 1 part of sodium carboxymethyl cellulose (Mw = 250,000 Daltons, degree of substitution = 0.7) in 30 parts of water, add 9 parts of potassium dihydrogen phosphate and 7 parts of urea, stir and mix well to obtain a mixed solution. Add the mixed solution dropwise into a 3wt% aluminum sulfate solution at a volume ratio of 2:1. After the reaction is completed, vacuum dry and crush to obtain fertilizer powder.
[0091] The finished product of Example 3 was mixed with fertilizer powder in a weight ratio of 3:2 to obtain an experimental product; Place the test sample in a non-woven mesh bag and bury the mesh bag 5-6 cm below the plateau sandy soil. Under room temperature, the soil moisture is controlled at 30%. Conduct multiple groups of tests in parallel. Take out the mesh bags after different days, dry them at room temperature, and then take out the test sample from the mesh bag for nutrient determination.
[0092] The results showed that the nitrogen in the finished product was released quickly, with a release rate of 55.2% after 5 days, and the release rates of potassium and phosphorus after 5 days were 68.3% and 49.8% respectively. The release rates of nitrogen, potassium and phosphorus after 30 days were 90.3%, 82.6% and 78.5% respectively.
[0093] This indicates that the soil conditioner formed by adding the bentonite prepared by the present invention has a nutrient slow-release effect.
[0094] Experiment 3 The ratio of the live bacteria count of Bacillus subtilis to lactic acid bacteria is 2:1 (the effective live bacteria count in actual fertilizer testing is ≥ 200 million / g) and is mixed with peptone, potassium dihydrogen phosphate, glucose, diatomaceous earth and water to prepare a granular microbial agent to obtain an agricultural microbial agent.
[0095] The basic production process of agricultural microbial agents is as follows: according to the formula, the original strain is activated and expanded for cultivation, the fermentation tank is cleaned and air-purified and disinfected, the seed tank, fermentation tank and raw materials are sterilized, inoculated, and fermented. After the fermentation, the bacterial liquid is tested for bacterial count and various indicators, and then it is put into a storage tank and input into a spray dryer for drying and powdering. The bacterial powder is transported to a granulator to form granules. After the qualified size of the product is sampled and tested for various indicators, it is packaged into finished products and put into storage. The number of mold and foreign bacteria is ≤3.0×106, the rate of foreign bacteria is ≤30%, the fineness is ≥80%, the pH is 6.5-7.5, and the moisture is ≤20%.
[0096] Detection of effective bacterial cell release rate and survival rate of the agricultural microbial agent in the carrier Different microbial carrier materials were selected, agricultural microbial agents were added at the same mass ratio, and the following detection method was used for the experiment. Among them, the present invention selected talcum powder group, bagasse group, sodium bentonite group, and Example 3.
[0097] Bacteria release rate detection method: Store the bacterial agent in a cool place. After two days, take 10g of sample and add 100mL of physiological saline to shake at 200r / min for 2h, then immediately determine the number of released bacteria by dilution plate counting method. Compare the number of inoculated bacteria with the number of released bacteria (the actual number of effective live bacteria in the carrier during the determination) to calculate the release rate. The results are shown in Table 2: Table 2 Bacteria release rate of different microbial carrier materials Grouping Inoculation number Number of released bacteria Release rate (%) Talc group <![CDATA[2.65×10 9 ]]> <![CDATA[2.19×10 9 ]]> 82.53 Bagasse Group <![CDATA[8.42×10 8 ]]> <![CDATA[4.46×10 6 ]]> 0.53 Sodium bentonite group <![CDATA[3.92×10 9 ]]> <![CDATA[3.08×10 9 ]]> 78.62 Example 3 <![CDATA[3.24×10 9 ]]> <![CDATA[3.21×10 9 ]]> 99.03 Survival rate detection method: Take 10g of sample from the bacterial agent placed at room temperature at 2, 10, 20, 40, 80 and 100 days, add 100mL of physiological saline and shake at 200r / min for 2h. The sampling method is the same as above. Use the dilution plate count method to determine the number of live bacteria released at different times, and use the ratio of the number of bacteria to the initial number of bacteria as the bacterial survival rate. The results are shown in Table 3: Table 3 Survival rate of bacteria on different microbial carrier materials
[0098] It can be seen from the experimental results of bacterial release rate and survival rate that the number of effective live bacteria in the microbial inoculant to which the bentonite prepared by the present invention is added as a microbial carrier material is relatively high.
[0099] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing multi-functional agricultural bentonite, characterized in that: The following steps are involved: 1) The bentonite is crushed, passed through a 500-mesh sieve, and double sodiumized to obtain sodium-based bentonite; 2) sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water are put into a mixer, and mixed at a high speed of 800 to 1200 rpm for 30 to 60 minutes. After the mixture is obtained, it is dried in an oven at 110°C, ball-milled, and passed through a 400-mesh sieve to obtain primary bentonite; the mass ratio of the sodium bentonite, sodium carboxymethyl cellulose, modified carbon powder, sodium dodecylbenzene sulfonate, aluminum citrate, polyacrylamide and deionized water is 100 to 120: 0.2 to 1: 3 to 6: 0.1 to 0.2: 0.05 to 0.2: 5 to 6: 200 to 400; 3) Mixing sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth, calcining for 1 to 2 hours, and cooling to obtain activated bentonite powder; the mass ratio of the sodium bentonite, primary bentonite, magnesium oxide, microcrystalline cellulose and diatomaceous earth is 60 to 80:40 to 55:1 to 5:5 to 10:30 to 40; 4) The modified hemp fiber is crushed, passed through a 400-mesh sieve, and the sieve residue is taken to obtain a modified fiber powder; the coal slag and biogas residue are crushed separately, passed through a 400-mesh sieve, and mixed in a ratio of 3 to 5:1 to obtain a mixture; 5) Mixing the activated bentonite powder, the mixture, the modified fiber powder and deionized water to form a suspension; 6) Dissolve chitosan in 4-6% acetic acid solution to fully dissolve it, add the suspension thereto, treat with ultrasound for 60-90 minutes, react at a constant temperature for 1-2 hours, and dry to obtain multi-element agricultural bentonite.
2. The method for preparing a multi-component agricultural bentonite according to claim 1, characterized in that: The modified carbon powder includes modified wood carbon powder and modified coal carbon powder, and the mass ratio of the modified wood carbon powder to the modified coal carbon powder is 7:
3.
3. The method for preparing a multi-component agricultural bentonite according to claim 2, characterized in that: The preparation method of the modified wood carbon powder is: Add polyvinyl alcohol into water and stir evenly, let it stand for 4 to 6 hours, then stir for 10 to 20 minutes, the stirring speed is 800 to 1000 r / min, add fatty acid glyceride and coconut oil and stir for 2 to 3 minutes, the stirring speed is 300 to 500 r / min, then add hexadecyl trimethyl ammonium bromide and sodium hydroxide and stir for 2 to 3 minutes, the stirring speed is 300 to 500 r / min, N, N-methylene bis acrylamide and stir for 2 to 3 minutes, the speed is 300 to 500 r / min, then add wood charcoal powder while stirring, stir for 6 to 8 hours, the stirring speed is 500 to 600 r / min, after mixing, send it into granulation equipment, extrude it into granular carbon, bake the granular carbon to a moisture content of ≤5%, the baking temperature is 70 to 120°C, and the baking time is 6 to 10 hours; send the baked granular carbon into a crushing equipment for crushing, and sieve it after crushing to obtain modified wood charcoal powder.
4. The method for preparing a multi-component agricultural bentonite according to claim 2, characterized in that: The preparation method of the modified coal-based carbon powder is: Add urea, humic acid, sodium hexaphosphate, polyethylene glycol and sodium carbonate into water and stir evenly, let stand for 4 to 6 minutes, add sodium dodecyl sulfate and stir evenly, add coal-based columnar carbon while stirring, stir for 1 to 2 hours, bake until the moisture content is ≤5%, crush and sieve to obtain modified coal-based carbon powder.
5. The method for preparing a multi-component agricultural bentonite according to claim 1, characterized in that: The grinding medium used in the ball mill is a zirconium oxide ball, the diameter of the grinding medium is between 5 and 20 mm, and the mass ratio of the grinding medium to the material is 1:
2.
6. The method for preparing a multi-component agricultural bentonite according to claim 1, characterized in that: The preparation method of the modified hemp fiber is: Purified lignin, calcium titanate and ultrapure water were mixed, magnetically stirred for 10 minutes, and ultrasonically dispersed for 0.5 hours to obtain a mixed solution; The jute fiber was washed and drained in deionized water, and then transferred to an oven for drying at 50-60°C. After drying, it was chopped into 0.5-1 mm and passed through a 100-mesh sieve. The sieved jute fiber was immersed in a 1 mol / L sodium hydroxide solution with a solid-liquid mass volume ratio of 1g:5mL. After soaking for 12 hours, it was washed with distilled water until neutral. Then the jute fiber was obtained and placed in a constant temperature blast drying oven for drying at 60°C for 8 hours. The dried jute fiber was immersed in the mixed solution for 1 hour at room temperature with magnetic stirring. After washing with deionized water until neutral, it was placed in a vacuum drying oven at 60°C for 8 hours to obtain modified jute fiber.
7. A method for preparing the multi-component agricultural bentonite as claimed in any one of claims 1 to 5, and use of the multi-component agricultural bentonite in agriculture.
8. The use of the multi-component agricultural bentonite in agriculture as claimed in claim 7, characterized in that: The multi-functional agricultural bentonite is used as a soil conditioner, a fertilizer conditioner, a fertilizer carrier, a microbial agent carrier and a fertilizer granulator.
Citation Information
Patent Citations
A sand-fixing composition and its preparation method and application
CN108949182B
Sodium bentonite and double sodium modifying method for sodium bentonite
CN104986778A
Sodium bentonite additive and preparation method thereof
CN105036149A
Modified bentonite and preparation method thereof
CN106966404A
Method for utilizing waste as soil improvement agent for remediating desertification soil
CN108353563A